Predicting COVID-19 Vaccine Uptake - Elizaveta Pronkina; Daniel I. Rees (Institute of Labor Economics (IZA), 2022)
Although COVID-19 vaccines are safe and effective, many adults are hesitant or unwilling to use them. Drawing on data from the Survey of Health, Ageing and Retirement in Europe (SHARE) Corona survey, we examine the correlates of vaccine uptake among Europeans ages 50 and older. We find that self-reported trust and risk aversion are good predictors of COVID-19 vaccine uptake. By contrast, there is little evidence that either excess mortality during the pandemic or official case counts influenced whether SHARE Corona respondents were vaccinated against COVID-19.
Keywords: I12; I18; 330; vaccination; COVID-19; flu; SHARE